(Im)moral Symbols and (Im)moral Deeds: Defensive Strategies for Coping with Historical Transgressions of Group Heroes and Villains. (April 2021) - Ivanović, Jovan; Žeželj, Iris; Psaltis, Charis
In two post-conflict societies (Serbia and Cyprus), the authors investigated how people cope with in-group historical transgression when heroes and villains relevant for their collective identity are made salient in it. The authors set the events in foundational periods for Serbian (Experiment 1) and Greek Cypriot (Experiment 2) ethnic identity—that is, historical representations of the Battle of Kosovo (1389) and the Liberation Struggle (1955–1959), respectively. In both experiments, a between-subjects design was used to manipulate group membership (in-group or out-group) and representation of the salient character (hero, villain, or neutral) in fictitious but historically plausible accounts of transgressions. In Experiment 1 ( N  = 225), the participants showed more moral disengagement in the case of in-group historical transgressions than in the case of identical transgressions by an out-group, while the in-group hero was rejected less than all the other historical characters. Social identification based on in-group superiority moderated both observed effects in such a manner that they were more pronounced for participants perceiving their ethnic group as superior. In Experiment 2 ( N  = 136), historical transgression involving the in-group hero provoked the most moral disengagement and the least rejection of the group deviant. In-group superiority and in-group importance as distinct modes of social identification moderated these effects in such a way that they were more pronounced for high-identifying individuals. Taken together, the experiments show that the in-group hero, as a highly valued ethnic symbol, is exempt from the black sheep effect and the sanctions of critically attached group members. The authors discuss the implications of in-group heroes for political and educational communication.